Pengaruh CAR, NPF dan TBH Terhadap Pembiayaan Bagi Hasil Dengan Profitabilitas Variabel Moderasi - Amalia Azka, Ika; Zamzami, R. Mohd (Jurnal Etnik: Ekonomi-Teknik, 2022)
Mudharabah and musyarakah profit-sharing financing are trademarks of Islamic banks. In addition, profit-sharing financing is considered appropriate to move the real sector where later from this financing a direct relationship will be formed between the bank and the customer in terms of capital and the risks borne, so that people who want to open a business can benefit from profit-sharing financing. This study aims to determine the effect of capital adequacy, non-performing financing, and the level of profit sharing on profit sharing financing with profitability as a moderating variable. The population and sample used in this study are Islamic commercial banks with annual financial statements for the 2015- 2019 period. This study uses a quantitative approach with purposive sampling in sampling. The total sample selected was 40 samples. The analytical technique used in this study uses the statistical application of Eviews 9. From the results of the t-test analysis (partially) shows the results that capital adequacy, financing problems, the level of profit sharing do not affect profit sharing financing. From the results of the analysis of the F test (simultaneously) shows the results that together capital adequacy, non-performing financing, and the level of profit sharing affect profit sharing financing. From the results of the MRA test (moderated regression analysis) it shows that profitability does not moderate the relationship between capital adequacy and profitsharing rates with profit-sharing financing, while profitability moderates (weakens) the relationship between non-performing financing and profit-sharing financing.